Access to and engagement with cervical and breast screening services for women with disabilities in Aotearoa New Zealand. Issue 10 (8th May 2022) - Pearson, Janet; Payne, Deborah; Yoshida, Karen; Garrett, Nicholas
Abstract: Purpose: To describe access to and engagement with cervical and breast screening services for women who are Deaf or live with a physical or sensory disability in Aotearoa New Zealand (NZ). Method: We carried out an online survey on a convenience sample of 84 women. Tests of association were undertaken between socio-demographics and cervical and breast screening; and between disability type, and health outcomes and barriers to screening respectively. Participants also reported specific barriers to screening. Results: Living without family/partner and unemployment were associated with never having a cervical smear. Non-English preferred language, and urban residence were related to lower levels of breast self-examination; having insufficient income was related to never having a mammogram. Disability type was not related to either smear or mammogram on eligibility, uptake ever, or uptake timeframe. A higher proportion of those with multiple disability types experienced service environment barriers to having a cervical smear. Specific barriers to screening covered accessibility, service environment, and information. Conclusions: This study, unique in Aotearoa, provides insights into disabled women's access to and engagement with screening services and suggests factors that may inhibit or facilitate participation. Women with multiple disabilities may be disadvantaged in the seeking and delivery of screening. Implications for rehabilitation: Rehabilitation and other practitioners need to be attuned to how women living with multiple disabilities may be disadvantaged in the seeking of, and, more importantly, the delivery of breast or cancer screening. Practitioners need to discuss with disabled women what supports or resources they need to have screening procedures, and to advocate for these supports for their clients. Practitioners need to ensure accessibility that encompasses the whole screening journey from the initial invitation to the obtaining of results. For practitioners to be able to provide equitable service delivery, the government and institutional policies and procedures that are developed must take into consideration the multiple needs of women living with disabilities.